Estudo de caso da modernização dos relés de proteção da Usina Hidroelétrica de Curuá-Una - NEVES, Erison Vilhena das (2018)
This work presents the main functions protections applied in generators machines 01 and 02, theHydroelectric Plant Curua-Una. With the advent of technology and the advantages that technological innovations were bringing to the electrical system, it has been found feasible to replace electromechanical relays obsolete by digital microprocessor.Like every insertion of something new, positive impacts were observed for the protection system. Thus, a case study was performed post-fault, indicating that the digital multifunction relay acted more during the year 2013 was the transformer. A chart was created to exemplify the result.